If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x-3x+84=12x+36
We move all terms to the left:
12x-3x+84-(12x+36)=0
We add all the numbers together, and all the variables
9x-(12x+36)+84=0
We get rid of parentheses
9x-12x-36+84=0
We add all the numbers together, and all the variables
-3x+48=0
We move all terms containing x to the left, all other terms to the right
-3x=-48
x=-48/-3
x=+16
| x.1.5=9/4.5 | | 38=8+6j | | C+3c=2 | | 0=-16t^2+80t-29 | | 0=-16t^2-80t-29 | | -3(d-4)=-2d-2(8=+4d) | | 5x−2=−8 | | y/7+13=21 | | 4(c+3c)=2 | | x3+x6=11 | | 7x27=90 | | 52/5+v=71/2 | | y-2/30=4/15 | | 2x*3=5x-2/7 | | 5x+4x(-)6x=24 | | 5n+5=85 | | 44+16n=-6n+27 | | 45=t+7 | | 92x+78=90 | | 38-x=30 | | 54=52+x | | .3n=12.6 | | 3•5=m/4 | | 34+p+12=78 | | 3x÷5=2x÷5+10 | | −4(−11+4n)=3(−2n+9) | | 16b–6.5=9.5 | | x-(13)=48 | | 120-6-2n=40 | | n^2-84=5n | | 16-x=15-8 | | 12v×6=32v×2+16 |